2020
DOI: 10.1111/jse.12562
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny, biogeography, and morphological ancestral character reconstruction in the Mediterranean genus Fumana (Cistaceae)

Abstract: Fumana is a diverse genus of the Cistaceae family, consisting of 21 currently accepted species. In this study, nuclear (ITS) and plastid (matK, trnT-L) molecular markers were used to reconstruct the phylogeny and to estimate divergence times, including 19 species of Fumana. Phylogenetic analyses (Bayesian Inference, Maximum Parsimony and Maximum Likelihood) confirmed the monophyly of Fumana and did not support the infrageneric divisions previously established. The results support four main clades that group sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…According to the nuclear tree, the split that gave rise to the Mediterranean Cytinus occurred around 26 Myr (Figure 2), which is strikingly similar to the crown age of the Cistaceae, the host family for Cytinus in this region (23–28 Myr; Aparicio et al, 2017). It has been suggested that the western Mediterranean was the main centre of diversification of the Cistaceae family and that the ancestors of most extant Cistaceae were initially present in south‐eastern Iberia and North Africa during the Miocene, under pre‐Mediterranean environmental conditions (Carrio et al, 2020; Guzman & Vargas, 2009; Martín‐Hernanz et al, 2021). The western Mediterranean may have been colonized by the ancestral palaeotropical Cytinus lineage via dispersal events across sub‐Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the nuclear tree, the split that gave rise to the Mediterranean Cytinus occurred around 26 Myr (Figure 2), which is strikingly similar to the crown age of the Cistaceae, the host family for Cytinus in this region (23–28 Myr; Aparicio et al, 2017). It has been suggested that the western Mediterranean was the main centre of diversification of the Cistaceae family and that the ancestors of most extant Cistaceae were initially present in south‐eastern Iberia and North Africa during the Miocene, under pre‐Mediterranean environmental conditions (Carrio et al, 2020; Guzman & Vargas, 2009; Martín‐Hernanz et al, 2021). The western Mediterranean may have been colonized by the ancestral palaeotropical Cytinus lineage via dispersal events across sub‐Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the western Mediterranean was the main centre of diversification of the Cistaceae family and that the ancestors of most extant Cistaceae were initially present in south-eastern Iberia and North Africa during the Miocene, under pre-Mediterranean environmental conditions (Carrio et al, 2020;Guzman & Vargas, 2009;Martín-Hernanz et al, 2021). The western Mediterranean may have been colonized by the ancestral palaeotropical Cytinus lineage via dispersal events across sub-Saharan Africa.…”
Section: Migrations To Warm Temperate Latitudesmentioning
confidence: 99%